1998
DOI: 10.1070/rc1998v067n03abeh000228
|View full text |Cite
|
Sign up to set email alerts
|

Metal ions as enzyme effectors

Abstract: The role of metal ions as enzyme effectors is considered. Data on inhibitory and activating effects of metal ions are summarised. The dual character of action of the effectors depend ing on their concentration and the nature of the enzyme is highlighted. The analytical applications of these effects are discussed. The bibliography includes 66 references.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
0
7
1
1
Order By: Relevance
“…This depends not only on the nature of the metal and the enzyme, but also on other specific conditions. The most important of those are various factors like the concentration of the metal [33]. During this study, it was not observed a significant effect in the concentration of metals indicating that CALB is not a metalloenzyme.…”
Section: Discussioncontrasting
confidence: 48%
“…This depends not only on the nature of the metal and the enzyme, but also on other specific conditions. The most important of those are various factors like the concentration of the metal [33]. During this study, it was not observed a significant effect in the concentration of metals indicating that CALB is not a metalloenzyme.…”
Section: Discussioncontrasting
confidence: 48%
“…Catalase has a metal ion in the active site. Addition of other metal ions to the enzyme might affect the stability of the structure or affect the redox state of metal in active site leading to a change in activity [33]. The Fe 3+ and Cu 2+ metal ions inhibited the activity of catalase progressively with the increase in the concentration of respective metal ions.…”
Section: Effect Of Inhibitors and Metal Ions On Catalase Activitymentioning
confidence: 99%
“…5 mM (137%, 115%) and declined at 2.0 mM (114%, 74%) metal ion concentration. The increase in catalase activity in the presence Ni 2+ , Ca 2+ , Mg 2+ and Mn 2+ may be due to the stability attained in the enzyme structure at that particular concentration of metal ion, at which they might serve as cofactors [33].…”
Section: Effect Of Inhibitors and Metal Ions On Catalase Activitymentioning
confidence: 99%
“…1 Determination of heavy-metal ions in owing freshwater sources has been of great importance, as heavy metals are highly toxic at high concentrations. 2 Bioaccumulation 3 of heavy metals in ora and fauna can change the non-lethal dose to lethal levels.…”
Section: Introductionmentioning
confidence: 99%